Calcium Alginate and Calcium Alginate-Chitosan Beads Containing Celecoxib Solubilized in a Self-Emulsifying Phase - Lorena Segale; Lorella Giovannelli; Paolo Mannina; Franco Pattarino (Scientifica)
In this work alginate and alginate-chitosan beads containing celecoxib solubilized into a self-emulsifying phase were developed in order to obtain a drug delivery system for oral administration, able to delay the drug release in acidic environment and to promote it in the intestinal compartment. The rationale of this work was linked to the desire to improve celecoxib therapeutic effectiveness reducing its gastric adverse effects and to favor its use in the prophylaxis of colon cancer and as adjuvant in the therapy of familial polyposis. The systems were prepared by ionotropic gelation using needles with different diameters (400 and 600 μm). Morphology, particle size, swelling behavior, and in vitro drug release performance of the beads in aqueous media with different pH were investigated. The experimental results demonstrated that the presence of chitosan in the formulation caused an increase of the mechanical resistance of the bead structure and, as a consequence, a limitation of the bead swelling ability and a decrease of the drug release rate at neutral pH. Alginate-chitosan beads could be a good tool to guarantee a celecoxib colon delivery.